The Gospel of John ; v. 1 - Barclay, William, 1907-78 (Edinburgh, Scoltand Saint Andrew, 1975)
Contents : v. 1 : chapters 1-7. Includes bibliographical references.
Keywords: Bible. N.T. John I-VII -- commentaries